2005
DOI: 10.1590/s0034-72992005000100012
|View full text |Cite
|
Sign up to set email alerts
|

Satisfação com a prótese auditiva na vida diária em usuários do Sistema de Saúde do Exército

Abstract: The objective of the present study was to investigate satisfaction levels with hearing aids in daily life of Army Health System users, in addition to associated factors. Adults and seniors from 3 rd Military Area that had purchased hearing aids within the years 1998 and 2003 were selected to answer SADL (Satisfaction with Amplification in Daily Life) questionnaire. We excluded patients aged less than 18 years; those that had acquired hearing aid for less than 6 weeks, and patients with severe comprehension and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
20

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 10 publications
(11 reference statements)
3
23
1
20
Order By: Relevance
“…Another feature that explained the decision regarding hearing aid use deals with the concept of satisfaction. Despite the technological advances of modern acoustic systems, user satisfaction remains a challenge for audiologists and the high rates of abandonment of hearing aid use remain a problem for health services (17) . Thus, monitoring satisfaction is important in the evaluation of clinical procedures and to ensure the quality of health services.…”
Section: Discussionmentioning
confidence: 99%
“…Another feature that explained the decision regarding hearing aid use deals with the concept of satisfaction. Despite the technological advances of modern acoustic systems, user satisfaction remains a challenge for audiologists and the high rates of abandonment of hearing aid use remain a problem for health services (17) . Thus, monitoring satisfaction is important in the evaluation of clinical procedures and to ensure the quality of health services.…”
Section: Discussionmentioning
confidence: 99%
“…Many concluded that the two week period after the fitting of hearing aids was insufficient to evaluate the results through the SADL (13) . In the current study, the first application of the questionnaire was conducted after a month of use, period also used in other studies (6)(7)(8)14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…It is comprised of six items (questions 1, 3, 5, 6, 9, 10); -Service and cost: assesses the speech-language pathologist and audiologist competence and the value of hearing aids. It is comprised of three items (12,14,15). Since this research was conducted with subjects who received hearing aids through concession, only the cost of batteries and transportation were considered; -Negative factors: covers three items that investigate performance in noisy environments, acoustic feedback and telephone use (questions 2, 7, 11); -Personal image: composed of three items analyzing the self-image of the hearing aid user and hearing aid stigma (questions 4, 8, 13).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, the SADL scale is short and brief but at the same time comprehensive enough to allow a valid evaluation of a multidimensional variable. Nevertheless, as Cox et al [3] point out, further researches are needed to refine the understanding and properties in test and retest and determine the clinical, scientific and administrative applicability of results [6]. Although there is no statistical significance in the comparative analysis between the groups of users monaural and binaural devices, it was observed that the individually, for both groups, the level of satisfaction was good.…”
Section: Discussionmentioning
confidence: 99%
“…1.278/MS of October 20, 1999, which Instituted programs of hearing devices (hearing aids) concession and public policies of cochlear implants [1,2] . They reveal what is beyond of the hearing aid performance showing the patient's perceptions of the device use in everyday communication situations, social life return, self-esteem improvement and overall health [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%